The anti-aging potential of antihypertensive peptides of Pariset, a dataset of algal peptides - Karimi, Isaac; Olfati, Parisa; Mohammed, Layth Jasim; Kadhim Tarrad, Jawad; Amshawee, Ahmed M.; Hussain, Maryam A.; Schiöth, Helgi B. (Frontiers in Aging, 2025)
IntroductionCellular senescence drives aging and disease by promoting inflammation and tissue dysfunction. The kidneys, highly susceptible to aging, worsen with hypertension, increasing chronic disease risk. Managing blood pressure with angiotensin-converting enzyme (ACE) inhibitors and natural bioactive peptides helps maintain kidney health. This study explores a kidney-associated aging network and algal peptides with renoprotective and anti-aging effects.MethodsSenescence-associated genes from Human Ageing Genomic Resources (HAGR) were used to construct and analyze a protein-protein interaction (PPI) network, refining a kidney-related subset ACE, angiotensin II Receptor Type 1 (AGTR1), and angiotensin II Receptor Type 2 (AGTR2). Algal antihypertensive peptides were filtered out of the laboratory dataset of algal peptides, Pariset, and assessed for allergenicity, antigenicity, toxicity, and anti-aging potential via sequence similarity searches. Selected peptides were prepared for molecular docking, tested against kidney-aging targets, and visualized.ResultsA senescence-associated PPI network revealed key aging-related proteins—IL1R, CD4, FN1, STAT3, CD45, APOE, CD44, ITGAM. CD8A, CD68, CDH1, ACE, AGTR1, and AGTR2—linked to inflammation, immunity, and fibrosis. Screening identified 54 antihypertensive peptides, among which seven were predicted to be non-allergenic and non-antigenic peptides, while six out of them exhibited anti-aging properties. KTFPY and others exhibited strong binding to ACE and kidney-aging proteins, suggesting therapeutic benefits.DiscussionThe senescence-associated PPI network reveals potentially important aging-related proteins affecting kidney health. Algal peptides, particularly KTFPY, VYRT, PGDTY, PVAFN, and MTFF, exhibit strong ACE binding, suggesting potential antihypertensive and anti-aging benefits. CD68 expressed reliable binding affinities with small-molecule ACE inhibitors, and it indicated the repurposing potential of these drugs for aging-associated conditions. These computational results highlight the potential of peptide-based therapies in addressing age-related kidney dysfunction, and warrant further experimental investigations.